Uji Organoleptik Spritz Cookies (Kue Semprit) dengan Tepung Mocaf sebagai Substitusi sebagian Tepung Terigu - I Made Rumadana; Alicia Alexandra Salu (JURNAL GASTRONOMI INDONESIA, 2020)
This research is about food experimental study which is preparing spritz cookies with mocaf (modified cassava flour) as an additional ingredient. Nurul (2019) said that Mocaf flour has various advantages including higher dissolved fiber content, higher calcium content and does not cause bloating. One of the advantages that people need to know is that mocaf flour is suitable for patients suffering from diabetes and obesity because the glycemic content is low and free of gluten. easy to be found, low in cost an good for avoiding degenerative dessease. The mixing process in making Spritz cookies by reducing the amount of flour by 25%, 50 % and 75 % of the flour in a recipe used and called as sample A,B and C. The result of the research by sensory evaluation showing that the flavour, taste, colour and texture of the sample A is better than sample B and C